Assistive Relief Tool for Early Childhood and Special Psychological Symptom Groups during the Pandemic: Clothing Design Based on the Virtual Contact Principle - Yunjuan Liu; Yan Wang; Meiyan Liu (Hindawi-Wiley, 2022)
During the COVID-19 pandemic, some special populations-groups of early childhood and people with autism, among others-faced more profound challenges than the common people. The lack of real physical contact such as embracing greatly affected the effectiveness of development, psychiatric treatment, and other processes for these populations. This study is aimed at developing clothing with appropriate contact pressure based on the contact comfort principle of psychology and providing a type of pressure clothing that can relieve the wearer's tension by simulating hugging, alleviating the lack of physical contact for early childhood education and special education groups during the pandemic. First, the elementary requirements of clothing design are attained using a questionnaire survey and test method. The analysis revealed that clothing should fulfill the four requirements of pressure comfort, fabric softness, wearing and taking off comfort, and visual beauty. Second, we realized the performance requirements in the fabric and accessories, style design, structure design, and functional design. Finally, the product experience is proposed through a fitting, and the reasonable opinions were fed back to the product design to enhance the functionality of clothing. The research shows that clothing can simulate hugging and can ease the loneliness of the wearer. This study can be used as a good tool to assist during the pandemic for early childhood education and special psychological symptom groups, as well as a broader group of people living alone at home, to play an adjunctive treatment and loneliness relief functions.